PPO.15 Comparing stillbirth rates in women who have regular scans and induction at term and those that have infrequent scans and induction post term. (9th June 2014) - Mone, F; Toner, B; Ong, S
Abstract : Objective: To determine the incidence of stillbirth in women who have regular ante-natal ultrasound and induction at term compared to those that have infrequent scans and induction post-term. Study design: A retrospective observational study was performed in a tertiary centre with 5, 700 deliveries per annum. Data on all deliveries was collected via the Northern Ireland Maternity System Database. Only women with an apparently low risk pregnancy were included. Women who had private antenatal care often had frequent scans and delivery at term. Women who did not have private antenatal care had scans infrequently and delivery post term. The still birth rate was calculated for both groups of women from 2007 to 2011 and compared using a Chi-squared analysis. Results: Our study included 23, 519 'low-risk' deliveries spanning 2007–2011. This included 2, 088 (9%) patients who had frequent ultrasound surveillance and delivery at term and 21, 431 (91%) patients who did not. The overall stillbirth rate was 0.34% and 0.20% respectively which was not statistically different (p = 0.31). Conclusion: There is no difference in the rate of stillbirth between patients who have more frequent ante-natal ultrasound surveillance and delivery at term compared to those who do not.